Dynamics and Trends in Research on Household Exposure to Second-Hand Smoke and Its Impact on Children’s Health: A Bibliometric Analysis - Kartika Puteri Cahyati; Titih Huriah (Universitas Pahlawan Tuanku Tambusai, 2026)
Household exposure to secondhand smoke (SHS) remains a major global public health issue, particularly among children who are more vulnerable due to their developing respiratory and immune systems. This study aims to analyze the dynamics and research trends related to household SHS exposure and its impact on children's health using a bibliometric approach. A quantitative bibliometric design was applied using secondary data from the Scopus database. Articles published between 2015 and 2025 were selected based on predefined criteria. Data were analyzed using VOSviewer to map co-authorship, citation networks, and keyword co-occurrence, while Microsoft Excel was used for descriptive trend analysis. The number of publications has increased significantly over time, with major contributions from developed countries such as the United States and the United Kingdom. Key research themes include SHS exposure, child health, respiratory diseases, and household environmental factors, with emerging focus on prevention and tobacco control policies. Research on SHS exposure has evolved into a multidisciplinary field. Strengthening policies and increasing public awareness are essential to reduce SHS exposure among children.